G Gender Analysis: of Polygamy Permit Based on the Reason of Benefit: (Case Study of Verdict Number: 0779/Pdt.G/2019/PA.Pwt)" - Supraptiningsih, Umi; Rahmawati, Theadora; Fauzi, M. Mahrus; Zainab, Laily (Nurani, 2023)
Case Number 0779/Pdt.G/2019/PA.Pwt is interesting to discus because int his case, the applicant's first wife allowed her husband to practice polygamy despite the fact that she can carry out her obligations as a wife, give birth, and she is not disabled or suffering from an incurable disease ( as the conditions contained in the Compilation of Islamic Law). The purpose of this paper is to examine the maslaha of the first wife in allowing polygamy. This research is classified as normative legal research, with a case study approach and some literature reviews derived from laws and regulations, books, official documents, journals, and research findings. The data sources used in this research are primary, secondary, and tertiary data sources. This research shows that the judge's consideration is based on the main reason of the applicant, husband, for asking polygamy because his wife is deemed unable to fulfill his Biological needs regularly which only fulfill for once or twice per week. Because of this, the court argue that the applicant’s proposal for polygamy has satisfied the provisions of Article 4 paragraph (2) letter A of Law No. 1 year 1974 concerning Marriage which is in line with the provisions of Article 57 letter A Compilation of Islamic. From the gender analysis, the decision did not show justice for the respondent, it was normal for biological relations to be fulfilled twice in one week, but the judge did not see the side of the applicant who experienced hypersex, however, the respondent still stated that he did not mind polygamy.